The central oscillatory network of orthostatic tremor. Issue 10 (7th August 2013) - Muthuraman, Muthuraman; Hellriegel, Helge; Paschen, Steffen; Hofschulte, Frank; Reese, Rene; Volkmann, Jens; Witt, K.; Deuschl, G.; Raethjen, Jan
ABSTRACT Orthostatic tremor (OT) is a movement disorder of the legs and trunk that is present in the standing position but typically absent when sitting. The pathological central network involved in orthostatic tremor is still unknown. In this study we analyzed 15 patients with simultaneous high‐resolution electroencephalography and electromyography recording to assess corticomuscular coherence. In 1 patient we were able to simultaneously record the local field potential in the ventrolateral thalamus and electroencephalography. Dynamic imaging of coherent source analysis was used to find the sources in the brain that are coherent with the peripheral tremor signal. When standing, the network for the tremor frequency consisted of unilateral activation in the primary motor leg area, supplementary motor area, primary sensory cortex, two prefrontal/premotor sources, thalamus, and cerebellum for the whole 30‐second segment recorded. The source coherence dynamics for the primary leg area and the thalamic source signals with the tibialis anterior muscle showed that they were highly coherent for the whole 30 seconds for the contralateral side but markedly decreased after 15 seconds for the ipsilateral side. The source signal and the recorded thalamus signal followed the same time frequency dynamics of coherence in 1 patient. The corticomuscular interaction in OT follows a consistent pattern with an initially bilateral pattern and then a segregated unilateral pattern after 15 seconds. This may add to the feeling of unsteadiness. It also makes the thalamus unlikely as the main source of orthostatic tremor. © 2013 International Parkinson and Movement Disorder Society